Parsley production using organic sources of phosphorus - Machado, Guilherme Gonçalves [UNESP]; Luis, Débora Cristina Mastroleo [UNESP]; da Silva, Irene Santos Slusarz [UNESP]; Pimenta, Lucas Daniel [UNESP]; Possas de Souza, Emanuele [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2024)
Parsley is a condiment produced mainly by small producers, often in the organic system. Organic fertilizers make nutrients slowly available to plants when compared to inorganic fertilizers, an important quality for phosphorus (P), which is a nutrient that tends to fixate and adsorption. Thus, the objective of this work was to evaluate the production of parsley with the use of organic sources of phosphorus in different proportions. Fourteen treatments were evaluated, resulting from the factorial 6 x 2 + 2: six proportions of two phosphate fertilizers (thermophosphate Yoorin® (TY) and bone meal (BM)), two doses (recommended (180 kg.ha-1 of P2O5, and double this) + two controls (without phosphate fertilizer; and with inorganic triple superphosphate fertilizer (recommended dose)). The proportions were: 100% P with TY; 80% P with TY + 20% with BM; 60% P with TY + 40% with BM; 40% P with TY + 60% with BM; 20% P with TY + 80% with BM; 100% P with BM. Shoot height, number of leaves, fresh and dry weight of leaves in two harvests and the total of these two harvests were evaluated. No significant differences were obtained in the two harvests. The lack of effect to phosphate fertilization may be related to the high initial P content in the soil (123 mg.dm-3), which shows that in this case, fertilization with this nutrient is not necessary to produce parsley, despite the official recommendation to fertilize with phosphorus in a soil with a high P content.
Keywords: Bone meal; Organic farming; Petroselinum crispum; Thermophosphate